Treatment of Purulent-Necrotic Soft Tissue Complications in Diabetic Foot (Eurasian Medical Research Periodical, 2023)
One of the frequent complications of diabetes mellitus (DM) is the lesion of human blood vessels, leading to the development of diabetic foot. Literature data and daily practical observation show an increase in the frequency of diabetic foot (30-70%), which raises the urgency of the issue of this disease treatment. This article contains data on the results of surgical treatment of 151 diabetic patients complicated with diabetic foot and purulentnecrotic inflammations of soft tissues. Our work presents the basic principles of treatment of purulent-necrotic complications of diabetes mellitus. The effectiveness of local application of Acerbin solution and two-stage surgical tactics in the complex surgical treatment of purulent-necrotic complications of diabetes mellitus has been proved.